Preparation, characterization and in vitro release study of BSA-loaded double-walled glucose-poly(lactideco- glycolide) microspheres - Ansary, Rezaul Haque; Rahman, Md. Mokhlesur; Awang, Mohamed; Katas, Haliza; Ab. Hadi, Hazrina; Mohamed, Farahidah; Doolaanea, Abd Almonem; Yunus, Kamaruzzaman (Springer, 2016)
The aim of this study was to prepare a model protein, bovine serum albumin (BSA) loaded double-walled microspheres using a fast degrading glucose core, hydroxyl-terminated poly(lactide-co-glycolide) (Glu- PLGA) and a moderate-degrading carboxyl-terminated PLGA polymers to reduce the initial burst release and to eliminate the lag phase from the release profile of PLGA microspheres. The double-walled microspheres were prepared using a modified water-in-oil-in-oil-in-water (w/o/o/w) method and singlepolymer microspheres were prepared using a conventional water-in-oil-in-water (w/o/w) emulsion solvent evaporation method. The particle size, morphology, encapsulation efficiency, thermal properties, in vitro drug release and structural integrity of BSA were evaluated in this study. Double-walled microspheres prepared with Glu-PLGA and PLGA polymers with a mass ratio of 1:1 were non-porous, smooth-surfaced, and spherical in shape. A significant reduction of initial burst release was achieved for the double-walled microspheres compared to single-polymer microspheres. In addition, microspheres prepared using Glu- PLGA and PLGA polymers in a mass ratio of 1:1 exhibited continuous BSA release after the small initial burst without any lag phase. It can be concluded that the double-walled microspheres made of Glu-PLGA and PLGA polymers in a mass ratio of 1:1 can be a potential delivery system for pharmaceutical proteins.